Empowerment and Enrichment Principles in the Philosophy of Pucuk Rebung Motives of Karawang Gayo - Abidah Abidah; Al Misry; Luqmanulhaqim Luqmanulhaqim; Susidamaiyanti Susidamaiyanti; Isnawati Isnawati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The aim of this paper is to discover the principles or patterns of empowerment and enrichment in the philosophy of Pucuk Rebung (bamboo shoots) in the motives of Kerawang Gayo. The method of this research is ethnographic method with interview data collection techniques, and study of the kerawang gayo text. Respondents of the research were the chairman of the Gayo customary assembly, traditional leaders, and community leaders. The method used is an ethnographic domain analysis. The research results shows that there are 7 principles of empowerment and enrichment based on local wisdom of openwork gayo motives, namely enlargment and betterment, sustainable leading, professional assistance, competency rechargement, professional employee strategic placement, consistency strengthening and improvement maintenance. The research results shows that there are 7 principles of empowerment and enrichment based on local wisdom of openwork gayo motives, namely enlargment and betterment, sustainable leading, professional assistance, competency rechargement, professional employee strategic placement, consistency strengthening and improvement maintenance. The method used is an ethnographic domain analysis. The research results shows that there are 7 principles of empowerment and enrichment based on local wisdom of openwork gayo motives, namely enlargment and betterment, sustainable leading, professional assistance, competency rechargement, professional employee strategic placement, consistency strengthening and improvement maintenance. The method used is an ethnographic domain analysis. The research results shows that there are 7 principles of empowerment and enrichment based on local wisdom of openwork gayo motives, namely enlargment and betterment, sustainable leading, professional assistance, competency rechargement, professional employee strategic placement, consistency strengthening and improvement maintenance.